2015
DOI: 10.1590/0004-282x20150137
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to higher production of interleukin-6 through -174 G > C polymorphism predicts global cognitive decline in oldest-old with cognitive impairment no dementia

Abstract: Interleukin 6 (IL-6) is a pro-inflammatory cytokine upregulated in neurodegenerative contexts. The polymorphism IL-6 -174 G > C influences release levels of this cytokine. We aimed to evaluate the influence of IL-6 -174 G > C on global cognitive score of a group with cognitive impairment no dementia in one year of follow-up.Methods The subjects were categorized in two groups: short-term decline in global cognitive score and those with short-term stability or improvement. IL-6 174 G > C information wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Low-grade systemic inflammation is associated with aging, and it has been described in patients with obsessive-compulsive disorder, major depression, bipolar disorder, Parkinson disease, and Alzheimer disease ( 50 53 ). Interleukin-6 (IL-6) was found to be increased systemically in patients suffering from these psychological diseases and correlates with the finding that old individuals that express more IL-6 develop cognitive decline more frequently ( 54 ). These findings indicate that the immune system detects homeostatic imbalances in the nervous system and is influenced by these imbalances, suggesting that homeostasis and function of immune and nervous systems are largely dependent on each other.…”
Section: Interaction and Evolution Of Immune And Nervous Systemsmentioning
confidence: 77%
“…Low-grade systemic inflammation is associated with aging, and it has been described in patients with obsessive-compulsive disorder, major depression, bipolar disorder, Parkinson disease, and Alzheimer disease ( 50 53 ). Interleukin-6 (IL-6) was found to be increased systemically in patients suffering from these psychological diseases and correlates with the finding that old individuals that express more IL-6 develop cognitive decline more frequently ( 54 ). These findings indicate that the immune system detects homeostatic imbalances in the nervous system and is influenced by these imbalances, suggesting that homeostasis and function of immune and nervous systems are largely dependent on each other.…”
Section: Interaction and Evolution Of Immune And Nervous Systemsmentioning
confidence: 77%
“…Recently, we demonstrated that the SNP IL‐6 −74G > C is involved in short‐term cognitive decline among CIND individuals. In this way, carriers of the C higher allele showed a three higher risk for cognitive decline at the 1‐year follow‐up compared with individuals with the GG lower genotype (Fraga et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is a pro-inflammatory cytokine that participates in inflammatory reactions and immune response and influences the growth and differentiation of cells in the central nervous system. Various studies have indicated increased peripheral IL-6 levels to be associated with cognitive impairment 27 , 28 . Furthermore, studies have shown that IL-6 may directly inhibit human hippocampal neurogenesis 29 .…”
Section: Introductionmentioning
confidence: 99%